2016
DOI: 10.1111/ene.13161
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in early Parkinson's disease: the Norwegian ParkWest study

Abstract: Fatigue is a common symptom in PD, also in early, untreated patients. During the first year of observation, an improvement in the fatigue scores was found. The improvement could not be attributed to a change in disease severity or depressive symptoms. The results indicate a better effect of dopamine agonists than of levodopa. This may have implications for treatment in patients with PD-associated fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…In case of articles stemmed from the same databases, only the primary (first) of these was included in the meta‐analysis to prevent a disproportional influence of some databases on overall estimate.…”
Section: Methodsmentioning
confidence: 99%
“…In case of articles stemmed from the same databases, only the primary (first) of these was included in the meta‐analysis to prevent a disproportional influence of some databases on overall estimate.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the diffusion of the different criteria, the UKPDSBB criteria have been widely employed in both clinical trials and routine clinical practice around the world, whereas, to the best of our knowledge, only a small number of clinical studies (mainly carried out in the US and in Scandinavia) have adopted Gelb criteria ( 26 33 ), somehow justifying their more limited diffusion among practicing clinicians. Calne criteria and Larsen criteria have been used even less.…”
Section: Diagnostic Accuracy Of Different Sets Of Criteriamentioning
confidence: 99%
“…The effects of dopaminergic agonists on fatigue are uncertain, and fatigue may even be an adverse effect of this type of medication . However, one study showed that treatment‐naïve patients had lower levels of fatigue after 1 year of treatment and that patients using dopaminergic agonists had greater benefit than those taking levodopa …”
Section: Treatmentmentioning
confidence: 99%